An unidentified emission in Titan's upper atmosphere. Issue 8 (29th April 2013) - Dinelli, B. M.; López‐Puertas, M.; Adriani, A.; Moriconi, M. L.; Funke, B.; García‐Comas, M.; D'Aversa, E.
Abstract : [1] We have analyzed limb daytime observations of Titan's upper atmosphere at 3.3 μ m, acquired by the visual‐infrared mapping spectrometer (VIMS) on Cassini. They were previously studied by García‐Comas et al. (2011) to derive CH4 densities. Here, we report an unidentified emission peaking around 3.28 μ m, hidden under the methane R branch. This emission is very strong, with intensity comparable to the CH4 bands located in the same spectral region. It presents a maximum at about 950 km and extends from 600 km up to 1250 km. It is definitely pumped by solar radiation since it vanishes at night. Our analysis shows that neither methane nor the major hydrocarbon compounds already discovered in Titan's upper atmosphere are responsible for it. We have discarded many other potential candidates and suggest that the unidentified emission might be caused by aromatic compounds. Key Points: We observe an unknown emission in VIMS spectra of Titan's upper atmosphere The feature is persistent, very strong, present at daytime and peaks at 950 km Not caused by known Titan gases, aromatic hydrocarbons are likely carriers